The Correlation of Television Show and Bullying Behavior in High School of Mahaputra in Makassar - Suryani Suryani; Andriani Andriani; Rosyidah Arafat (Indonesian Contemporary Nursing Journal, 2018)
Introduction: Bullying is an experience  that occurs when the helplessness  persecuted  by the others behaviour and afraid of the repected bad behaviour and ill do it is repeated. One of causes bullying behavior is a television show, this can occur because television show that is presented is very diverse, so that school children is free to watch their favorite television show. This study aimed to determine the relationship between television show with bullying behavior in student of class XI and XII in SMA Maha Putra Makassar. Method: This study using  cross  sectional  method.  The  total  study  populations   130  and  samples  are  98 respondents with purposive sampling technique. Data analyzed were using the Chi-Square.  Result: In this study showed that there is no relationship  between television  show with bullying  behavior  in  student  of  class  XI  and  XII  in  Maha  Putra  Senior  High  School Makassar. Conclusions: Level bullying dominant is low level with the  bullying  often  is  verbal  bullying,  and  program  often  that  watched  is  soap  opera. Therefore, they are expected to do more introduce of bullying to students.